2005
DOI: 10.1046/j.1540-8167.2005.40427.x
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Characteristics of hERG, hNav1.5, and hKvLQT1/hminK after Administration of the Novel Anti‐Arrhythmic Compound AZD7009

Abstract: AZD7009 inhibits both the hERG and the hNav1.5 current, and it is most likely this combined current block that underlies the prolongation of the refractoriness and the low proarrhythmic activity demonstrated in animals in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…[12][13][14] AZD7009 was in clinical development for conversion of atrial fibrillation to sinus rhythm and showed low proarrhythmic potential and very promising antiarrhythmic efficacy in patients with atrial fibrillation episodes lasting up to 3 months but was recently discontinued clinical development for noncardiovascular reasons. 15,16 Actually, in a subgroup of patients with atrial fibrillation lasting for one month the conversion rate was 82%, similar to the conversion rate seen in the placebo-treated patients subjected DC cardioversion (83% conversion rate).…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] AZD7009 was in clinical development for conversion of atrial fibrillation to sinus rhythm and showed low proarrhythmic potential and very promising antiarrhythmic efficacy in patients with atrial fibrillation episodes lasting up to 3 months but was recently discontinued clinical development for noncardiovascular reasons. 15,16 Actually, in a subgroup of patients with atrial fibrillation lasting for one month the conversion rate was 82%, similar to the conversion rate seen in the placebo-treated patients subjected DC cardioversion (83% conversion rate).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were repeated three times. When used, tetrodotoxin (500 mol/l, Sigma) (27,30) (20 mol/l), ANG II (100 nmol/l) alone, or combined with apocynin (100 mol/l), polyethylene glycol-conjugated catalase (PEG-CAT; 50 U/ml), 4,5-dihydroxy-1,3-benzene disulfonic acid (tiron;10 mmol/l) or 4-hydroxy-2,2,6,6-tetramethylpiperidine-N-oxyl (Tempol; 3 mmol/l) for 48 h. Total RNA from untreated and treated cardiomyocytes was isolated using the RNeasy Mini Kit (Qiagen, Valencia, CA) with the addition of RNase-free DNase I. Reverse transcription was carried out at 42°C for 30 min with iScript reverse transcriptase (Bio-Rad, Hercules, CA), 1 g total RNA, and 4 l of 5ϫ iScript reaction mix following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the minor structural differences in AZD1305 versus AZD7009 introduce potent I CaL activity to the I Kr -and I Na -blocking characteristics described for both agents. 7,8,17 Hence, with its combined ion channel-blocking profile, AZD1305 has been proposed as an antiarrhythmic agent against AF with a lower proarrhythmic potential than other antiarrhythmic drugs. AZD1305 has been demonstrated to cause atrial-predominant effects in the …”
Section: Discussionmentioning
confidence: 99%